2007
DOI: 10.1108/03090560710821224
|View full text |Cite
|
Sign up to set email alerts
|

Consumer complaint behaviour of Asians and non‐Asians about hotel services

Abstract: PurposeThis paper aims to test the differences in the consumer complaint behaviour of Asian and non‐Asian hotel guests in terms of culture dimensions. It also aims to examine the relationship between demographic factors (age, gender and education level) and complaint behaviour.Design/methodology/approachThe paper adopts the Hofstede's typology of culture as a framework to investigate cultural differences and demographic characteristics in the complaint behaviour of hotel guests. A face‐to‐face interview survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
161
4
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 20 publications
(45 reference statements)
12
161
4
15
Order By: Relevance
“…However, this result contradicts the findings of previous studies claiming that Asian, specifically Chinese, are less likely to complain and are only inclined to take private action instead of public action (Ngai et al, 2007;Fitzpatrick, Davey, & Dai, 2012).…”
Section: Customer Complaint Responses That Are Expressed In Asian Fulcontrasting
confidence: 57%
See 2 more Smart Citations
“…However, this result contradicts the findings of previous studies claiming that Asian, specifically Chinese, are less likely to complain and are only inclined to take private action instead of public action (Ngai et al, 2007;Fitzpatrick, Davey, & Dai, 2012).…”
Section: Customer Complaint Responses That Are Expressed In Asian Fulcontrasting
confidence: 57%
“…Despite the degree of dissatisfaction, 98% of the respondents stated that they prefer not to proceed with any public action. However, the reason behind such decision is inconsistent with the findings of previous scholars who posited that Asians fear of losing face (Ngai et al, 2007); rather, customers will not take public action mostly because it is not worth their time and effort (Day et al, 1981). Some respondents claimed that they will share the complaint with the Consumer Council in Hong Kong as part of taking public action.…”
Section: Customer Complaint Responses That Are Expressed In Asian Fulcontrasting
confidence: 55%
See 1 more Smart Citation
“…Although customer complaints are inevitable, customer satisfaction plays a vital role in sustaining the existence of hotel enterprises in the current highly competitive environment (Ngai et al, 2007). Barlow (1996) indicated that customer complaints are important for the improvement of hotel operators because complaints make operators aware of the problems, and thus, they are able to rectify them in a timely and spontaneous manner.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have investigated customer complaints and complaint behavior (Heung & Lam, 2003). Ngai et al (2007) studied the Consumer Complaint Behavior (CCB) of Asians and non-Asians toward hotel services. Hui & Au (2001) studied the complaint behavior of Chinese and Canadian tourists toward hotel services.…”
Section: Study Rationale and Objectivesmentioning
confidence: 99%